Variations in the Shape of the Coronoid Process in the Adult Human Mandible - Hossain, SM Akram; Hossain, SM Moshadeq; Banna, Fakhrul Amin Mohammad Hasanul (Bangladesh Journal of Anatomy, 2013)
DOI: http://dx.doi.org/10.3329/bja.v9i2.15275 Bangladesh Journal of Anatomy 2011 Vol.9(2) pp.75-78